A Risk Assessment Analysis to Enhance the Security of OT WAN with SD-WAN - Van Joshua Abergos; Faiza Medjek (Journal of Cybersecurity and Privacy)
This paper introduces a comprehensive risk assessment of various wide area network (WAN) technologies as applied to Operational Technology (OT) infrastructures, thus uncovering which WAN technology is best suited for OT to mitigate the risks of Denial of View (DoV), Denial of Control (DoC), and Denial of Service (DoS). A new risk weight-based evaluation approach is proposed following NIST CSF and ISA/IEC 62443 standard risk scoring (RS). In this approach, RS was modified by introducing new risk metrics, namely, risk (Rn), mitigation (Mm), risk prioritization (WRn), and mitigation prioritization (WMm) to create a specialized probability formula to assess risks on OT WAN infrastructure. The proposed formula has been implemented to automate data analysis and risk scoring across nine WAN technologies. The obtained results demonstrated that software-defined wide area network (SD-WAN) has the best security features that even overshadow its vulnerabilities to perform not just as a WAN solution but as a security solution against DoV, DoC, and DoS. Furthermore, this paper identifies and highlights what to prioritize when designing and assessing an SD-WAN setup. In addition, this paper proposes an SD-WAN-based architecture to reduce DoV, DoC, and DoS risks.